Suzuki–Miyaura Diversification of Amino Acids and Dipeptides in Aqueous Media. Issue 14 (29th June 2015) - Willemse, Tom; Van Imp, Karolien; Goss, Rebecca J. M.; Van Vlijmen, Herman W. T.; Schepens, Wim; Maes, Bert U. W.; Ballet, Steven
Abstract The Suzuki–Miyaura derivatisation of free amino acids, peptides and proteins is an attractive area with considerable potential utility for medicinal chemistry and chemical biology. Here we report the modification of unprotected and Boc‐protected aromatic amino acids and dipeptides in aqueous media, enabling heteroarylation and vinylation. We systematically investigate the impact of the peptide backbone and adjacent amino acid residues upon the reaction. Our studies reveal that although asparagine and histidine hinder the reaction, by utilising dppf, a ferrocene‐based bidentate phosphine ligand, cross coupling of halophenylalanine or halotryptophan adjacent to such a residue could be enabled. Our studies reveal dppf to have good compatibility with all unprotected, proteinogenic amino acid side chains.